Factors Influencing Foreign Direct Investment in Muslim Countries: The Role of Financial Developments - Hatim, Fajri; Muhamad, Nurdin I; Azzaki, Muhammad Adnan; Nasar, Fahima (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
ABSTRACT   Purpose: This research reviewed the determinant factor of FDI in OIC countries using a framework of institutional quality, green economic policies, and the role of financial development.Design/methodology: The method used in this research is panel data analysis with the Generalized Method of Moments (GMM) approach. This research examines 32 OIC countries with 352 observations in the period 2010 to 2022.Findings: The results of the research are generally show that institutional quality, green economic policies and the role of financial development attract foreign direct investment. However, there are still factors that cause low FDI flows, the causal factor is voice and accountability and control of corruption.Practical implications: The empirical implication of this research is to determine the conditions and factors that cause FDI inflows through institutional quality, green economy and financial development in OIC countries.Originality/Value: OIC countries should improved their institutional quality with policies oriented towards global investor preferences. The contribution of this research focuses on efforts to attract capital flows for the development of OIC countries